1986
DOI: 10.1161/01.cir.73.2.325
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of indium-111 platelet deposition on Dacron vascular grafts in humans by aspirin plus dipyridamole.

Abstract: Aspirin plus dipyridamole reduces platelet accumulation on short-term Dacron vascular grafts in man. To determine whether drug inhibition of platelet deposition is sustained on older grafts, we studied 18 men aged 41 to 87 years who had Dacron aortic bifurcation grafts in place a mean of 43.4 months (range 9.8 to 121.0) before and during short-term therapy with aspirin (325 mg tid) plus dipyridamole (75 mg tid). During both the baseline and drug studies, indium-111 (1'In) platelet deposition was quantitated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…Possibly, the lack of effect of aspirin plus dipyridamole in our present study may have been due to a reduction in prostacyclin generation by the pseudointima resulting from aspirin therapy at this dose. Interestingly, in a recent study involving greater numbers of patients, aspirin plus dipyridamole has been reported to marginally, but significantly, inhibit platelet deposition onto mature Dacron grafts (39). The 10% reduction in platelet deposition reported is much less than that observed with the combination of drugs in freshly implanted grafts (17,18) and is less impressive than the mean 40% reduction in TI of the mature grafts seen with AH23848 in the present study.…”
Section: Discussioncontrasting
confidence: 70%
“…Possibly, the lack of effect of aspirin plus dipyridamole in our present study may have been due to a reduction in prostacyclin generation by the pseudointima resulting from aspirin therapy at this dose. Interestingly, in a recent study involving greater numbers of patients, aspirin plus dipyridamole has been reported to marginally, but significantly, inhibit platelet deposition onto mature Dacron grafts (39). The 10% reduction in platelet deposition reported is much less than that observed with the combination of drugs in freshly implanted grafts (17,18) and is less impressive than the mean 40% reduction in TI of the mature grafts seen with AH23848 in the present study.…”
Section: Discussioncontrasting
confidence: 70%
“…The increase in bleeding time is regarded as both statistically and clinically insignificant. [36][37][38][39][40][41]. Activated platelets also accelerate the generation of thrombin about 280,000-fold by enabling the formation of the prothrombinase complex on the membrane surface (42).…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin, ticlopidine and prostacyclin nevertheless reduce the initial accumulation of platelets on freshly implanted grafts (38,40). One study has shown that the only drug regimen that diminishes platelet deposition on mature grafts (>9 months old) in humans is a combination of aspirin and dipyridamole (39). This remains a controversial issue, because in a recent clinical trial it was shown that aspirin/dipyridamole is not effective in the reduction of platelet deposition on mature Dacron grafts (45).…”
Section: Atherosclerotic Lesionsmentioning
confidence: 99%
“…139 -142 Other studies in patients with Dacron aortofemoral bypass prostheses show continued uptake of labeled platelets on these prostheses when studied years after implantation. 142,143 This points out the difference in healing responses between man and experimental animals, which develop an endothelialized neointima that completely covers the luminal surface of large aortic and iliac prostheses within months to years after implantation. 144 -146…”
Section: Vein Grafts and Arterial Prosthesesmentioning
confidence: 99%